Mechanical properties of amorphous Ge2Sb2Te5 thin layers - D'Arrigo, G.; Mio, A.; Favaro, G.; Calabretta, M.; Sitta, A.; Sciuto, A.; Russo, M.; Calì, M.; Oliveri, M.; Rimini, E. (Surface & coatings technology, 2018)
The working principle of a Phase Change Memory (PCM) cell exploits the repeated reversible transition between a crystalline and an amorphous phase of chalcogenide alloys typically Ge2Sb2Te5, that are characterized respectively by a high (SET) and a low (RESET) conductive state. The change in density between the two phases (6%) induces a very high compressive stress to the active amorphous region by the surrounding crystalline materials. Moreover, the physical iterative transformation between crystalline and amorphous phase transformation introduces a swelling and deswelling effect. This is one of the key failure mechanisms that are limiting the reliability of the final integration of the PCM system. Knowledge of the mechanical properties of the amorphous phase is then an important factor. Amorphous structure, i. e. its short-range order, depends on the adopted formation procedure. In this paper we analyze the mechanical characteristics of sputtered amorphous Ge2Sb2Te5 thin layers and the modification introduced by ion irradiation, a procedure adopted to simulate the amorphous state produced by melt quenching. Measurements of Young's Modulus and Hardness were performed using Ultra High-Nano Indentation on plane samples. The values of both quantities increase of about 10–20% in the 30 keV Ge+ irradiated samples. This trend is due to the reduction of homopolar wrong bonds (GeGe and TeTe) present in the as deposited film. Thermal spikes associated to the impinging ion cause a local atomic rearrangement that results in a structure similar to that of the crystalline phase. The investigation was extended to cantilevers of length in the range 10–200 μm, with a layer of 100 nm Ge2Sb2Te5 deposited on 280 nm thick SiN. The cantilever modal analysis and the out of plane deflection measurements were correlated using a Finite Element modeling, that makes use of the mechanical values measured by Ultra high Nano Indentation. After deposition the amorphous Ge2Sb2Te5 layer is subject to a compressive mechanical shrinkage, this internal stress is released after ion implantation. •Phase change materials are deeply studied as active layers in nonvolatile memories.•Ion irradiation is adopted to simulate the amorphous state produced by melt quenching.•Young's Modulus and Hardness were performed using Ultra High-Nano Indentation.•Phase structure change implies the cantilevers resonance frequency shift.•Boundary conditions modification are evidenced by out of plane deflection change.